Pengaruh Kompetensi SDM dan Teknologi Informasi Terhadap Loyalitas Pengunjung di Perpustakaan Daerah - Rahmawati, Anis (PT. Pustaka Cendekia Publisher, 2025)
This study aims to examine the influence of human resource (HR) competence and information technology on visitor loyalty at a regional library. The background of this research highlights the importance of service quality provided by librarians and the use of information technology to enhance visitor satisfaction and comfort. The research method used is quantitative, with a survey approach conducted through questionnaires distributed to library visitors. The data analysis technique used is multiple linear regression to determine the effect of each variable. The results show that both HR competence and information technology have a positive and significant effect on visitor loyalty. This means that the better the competence of the librarians and the more effective the use of technology, the higher the level of visitor loyalty to the regional library. Therefore, improving staff competence and service innovation through technology are crucial factors in maintaining and increasing community visits to the library.